Selection of natures for practical painting lessons and organization of the working space. - Mamitaliev Akhmadzhon Ganievich; Adkhamova Oltina Rafikjonovna (Genius Publishing Group, 2023)
This article presents one of the genres of fine art, the genre of still life, theory, the creative process in the subject, reflections on the specific features of painting from nature, the choice of types and places of work for practical classes in painting from nature, information about the organization of the working space and a number of methodical recommendations
Keywords: Still life; fine arts; student; teacher